Impact of environmental factors on efficiency of rice production in Bangladesh - Hossain, M.K.; Kamil, A.A.; Masron, T.A.; Baten, Md Azizul (AENSI Publisher, 2013)
This study uses environment variables in Data Envelopment Analysis (DEA) and examines the influence of environmental factors on efficiency of rice production in Bangladesh.Data was collected from Bangladesh Bureau of Statistics (BBS) and Bangladesh Meteorology Department Efficiency with and without environmental factors of three type of rice production (AUS, AMAN and BORO) are measured using data envelopment analysis.Efficiency of rice production which measured without environmental factors is explained by the environmental factors (Rainfall, Temperature and Humidity) using Tobit regression to weigh up the impact of these factors on rice production.Efficiency of BORO production with environmental factors is almost similar to the efficiency of production without environmental factors. Production efficiency of AUS and AMAN employing environmental factors is higher than that of without environmental factors. Humidity has a positive and significant effect on all types of rice production.Temperature has a negative impact on production efficiency, implying that global warming could be a cause for a decrease in efficiency of rice production.Rainfall has a positive impact only on BORO production.